2017
DOI: 10.1084/jem.20170976
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting hematopoietic and renal cell heterogeneity in adult zebrafish at single-cell resolution using RNA sequencing

Abstract: The work by Tang et al. provides a comprehensive, single-cell, transcriptomic analysis of kidney and blood cells from the adult zebrafish, identifying novel cell types, including two classes of NK immune cells, classically defined and erythroid-primed hematopoietic stem and progenitor cells, mucin-secreting kidney cells, and kidney stem/progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(206 citation statements)
references
References 52 publications
5
200
1
Order By: Relevance
“…However, B‐cell transcripts were also found in the lymphoid mpeg1.1 − cell population, suggesting that not all B lymphocytes express mpeg1.1 . To further explore the identity of lymphoid mpeg1.1 + cells, we turned to single‐cell analysis and examined transcript expression among individual hematopoietic cells using our previously reported single‐cell transcriptional profiling of zebrafish WKM . By querying this dataset, we first confirmed the existence of a mpeg1.1 + cluster associated with the B‐cell lineage (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, B‐cell transcripts were also found in the lymphoid mpeg1.1 − cell population, suggesting that not all B lymphocytes express mpeg1.1 . To further explore the identity of lymphoid mpeg1.1 + cells, we turned to single‐cell analysis and examined transcript expression among individual hematopoietic cells using our previously reported single‐cell transcriptional profiling of zebrafish WKM . By querying this dataset, we first confirmed the existence of a mpeg1.1 + cluster associated with the B‐cell lineage (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Whole‐kidney marrows were isolated from three separate adult wild‐type fish (3‐9 mo old) and subjected to inDrop single‐cell RNA sequencing https://molpath.shinyapps.io/zebrafishblood/…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50 most significantly differentially expressed genes (Wilcoxon rank-sum test) for the putative T cells include a number of T cell and immune markers (23) ( Figure 3B). We note that we did not observe significant expression of markers associated with other motile non-T immune cells (B cells, macrophages, or neutrophils) (23,24), and we do not find support for NK cells (Materials and Methods, Figure S6).…”
mentioning
confidence: 72%
“…scRNA-seq successfully distinguished not only the cell types of proximal tubules, loop of Henle, distal tubules, and collecting ducts, but also found that interferon scores based on tubular epithelial cells' scRNA-seq data of lupus nephritis patients correlate with renal clinical scores. Tang et al [75] performed scRNA-seq analysis of zebrafish kidney that was deficient in several genes and investigated the consequence of the gene deficiencies; in addition, they uncovered several novel cell types.…”
Section: Current Studies In the Field Of Kidney Research That Used Scmentioning
confidence: 99%